Implementation of Digital Transformation in Meatball MSMEs Malang City - Yogi Dwi Lestari; Yhadi Firdiansyah; Vida Maria Ulfa (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital transformation has become an urgent need for Micro, Small and Medium Enterprises (MSMEs) in the food and beverage sector, including meatball MSMEs in Malang City. This article discusses the level of digitalization of meatball MSMEs, factors influencing the adoption of digital technology, as well as the challenges and opportunities faced in the digital transformation process. By focusing on digital literacy, use of e-commerce, social media and delivery applications, this research provides an in-depth understanding of the actual conditions of digital transformation in meatball culinary MSMEs. This research provides an impact on the importance of digital transformation as a crucial step for Bakso MSMEs to remain relevant and competitive in the digital era.